Study of numerical analysis and gravimetric method of soil water contents in relation to growth parameters and yields of onions (Allium cepa L.) - Anda, P.; Hamimu, L.; Sabaruddin, L. (International Journal of Agricultural Technology, 2021)
Results showed that soil water contents were estimated with numerical model and gravimetric method revealed to follow very similar trends. Regression equations for datasets provided some insight into their similarities. Both the numerical model and the gravimetric method showed the two sets of quadratic equations with a mean correlation coefficient of 0.98 and a mean coefficient of determination of 0.99. All equations were very close in nature. Despite high levels of correlation for all simulations, it noted that numerical model was idealized as gravimetric method and the soil domain was assumed to uniform and unsaturated. Analysis of the correlation between the groundwater content of the numerical model and the gravimetric method appeared to be a strong correlation with a correlation coefficient of 0.96. Comparing the results of numerical analysis with the gravimetric method, the similarity level was closed to 80%. Thus, it concluded that the numerical estimation of soil water contents as an alternative method should be considered